El principio de igualdad en la aplicación de los beneficios para los procesados en el proceso penal - Zambrano Montenegro, Cristina Lizbeth; Montenegro Merino, Rosa Angelita (Machala: Universidad Tecnica de Machala, 2016)
El estudio de casos que llevamos a cabo, se lo realizó en base a un caso por delito de robo, pero más que analizar o discutir el tipo penal o el mismo proceso de juzgamiento, tomamos en cuenta una situación particular en la condena de un procesado. En el proceso penal seguido contra Luis Pineda Pauta y otros por el delito de Robo, se condenó al procesado a la pena de 6 años y ocho meses de pena privativa de libertad en el juicio en proceso penal directo, mientras que el resto de los procesados fueron condenados a la pena de 6 meses de pena privativa de libertad en el juicio mediante proceso penal abreviado. De la misma manera, los 3 procesados que fueron beneficiados con el proceso penal abreviado, fueron beneficiados con la suspensión condicional de la pena. La misma petición realizó el señor Luis Pineda Pauta y siendo procedente la misma y habiéndose ya negado el proceso penal abreviado, también le fue negada la petición de suspensión. En nuestra investigación hacemos una discusión de la aplicación del principio de igualdad en el proceso penal, y de cómo se debe tratar a los procesados cuando se trata de otorgarles los beneficios existentes en la ley.
The case study we conducted, it performed based on a case by robbery, but more than analyze or discuss the criminal or the same judging process, we consider a particular situation in the conviction of a defendant . In the criminal proceedings against Luis Pineda Pauta and others for the crime of theft, was sentenced the defendant to the penalty of six years and eight months' imprisonment in the trial live criminal proceedings, while the rest of the defendants They were sentenced to 6 months imprisonment in the trial by abbreviated criminal proceedings. Similarly, the 3 defendants who were benefited by the abbreviated criminal proceedings, were granted conditional suspension of sentence. The same request made by Mr. Luis Pineda Pauta and being from the same and having already denied the abbreviated criminal proceedings, also was denied the request for suspension. In our research we make a discussion of the application of the principle of equality in the criminal process, and how to treat the accused when it comes to granting benefits in existing law. Our main conclusion is that the judge was wrong and hurt too much to the defendant Luis Pineda who went on an unequal and discriminatory treatment because have passed court. The criminal process is par excellence the process where it becomes clear all the interpretive possibilities emanating from the Constitution of the Republic, the same as from the year 2008 is in force and inserted to Ecuador in the model neoconstitutional state. That is why equality as a principle should be immediately applied the criminal process can not consider any other factor of the person simple procedural circumstances, leaving aside their race, ethnicity, criminal record, employment status, etc. The unequal treatment has been a historically shameful reality for the state, since in many scenarios was evident as the lack of literal rule on treatment without discrimination remained excluded from the full enjoyment of their rights to several individuals and groups, which in the now it tries to leave aside, of course as a process, but it is imperative, much more it is for public servants and judges who are the law and the Constitution should apply.
Keywords: IGUALDAD; PROCESO; PENA